2014
DOI: 10.14481/jkges.2014.15.11.67
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Development of the Seismic Fragility Functions of the High Speed Railway Tunnels in use

Abstract: In this study, the staged seismic performance evaluations were conducted to the 91 high speed railway tunnels in use for checking whether to comply with the recent design criteria or not. In addition, the seismic fragility functions of the tunnels were developed to allow the probabilistic risk assessment. The results of the staged seismic performance evaluations which consist of a preliminary assessment and a detailed assessment, show that the tunnels comply with the recent design criteria. With reference to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Finally, the seismic vulnerability curve of the tunnel was obtained by applying the mathematical method of maximum likelihood estimation (MLE) [15]; Kim conducted seismic performance evaluation on the classification of Jinfu high-speed railway tunnels and established a seismic vulnerability curve for probabilistic risk assessment. The comparison showed that the seismic performance of the hidden excavation method tunnel was better than that of the cover excavation method tunnel, and the probability of each damage level was relatively low [16]; Mayoral conducted threedimensional finite difference nonlinear analysis using FLAC3D to obtain the seismic response of tunnel shafts under increasing seismic intensity, and established their seismic vulnerability curves [17]; Andreotti proposed a new cumulative damage index for deep buried tunnels to evaluate the degradation failure behavior of reinforced concrete under cyclic loading, and based on plastic concentration theory and multiple two-dimensional incremental dynamic analyses, simulated the seismic cumulative damage of tunnel lining [18].…”
Section: Research Statusmentioning
confidence: 99%
“…Finally, the seismic vulnerability curve of the tunnel was obtained by applying the mathematical method of maximum likelihood estimation (MLE) [15]; Kim conducted seismic performance evaluation on the classification of Jinfu high-speed railway tunnels and established a seismic vulnerability curve for probabilistic risk assessment. The comparison showed that the seismic performance of the hidden excavation method tunnel was better than that of the cover excavation method tunnel, and the probability of each damage level was relatively low [16]; Mayoral conducted threedimensional finite difference nonlinear analysis using FLAC3D to obtain the seismic response of tunnel shafts under increasing seismic intensity, and established their seismic vulnerability curves [17]; Andreotti proposed a new cumulative damage index for deep buried tunnels to evaluate the degradation failure behavior of reinforced concrete under cyclic loading, and based on plastic concentration theory and multiple two-dimensional incremental dynamic analyses, simulated the seismic cumulative damage of tunnel lining [18].…”
Section: Research Statusmentioning
confidence: 99%
“…Kim et al [50] developed PGA-based fragility curves for NATM tunnels, analysing numerically (by means of dynamic time-history analyses) the fragility of 91 newly built tunnels in Korea. Fragility curves were derived for distinct damage states, using the exceedance of capacity of the liners for the definition of the damage state thresholds.…”
Section: Mountain Tunnels and Tunnels In Rockmentioning
confidence: 99%
“…In addition to rock tunnels, Kim et al [50] developed PGA-based fragility curves for cut and cover tunnels, numerically analysing the fragility of newly built tunnels in Korea.…”
Section: Mountain Tunnels and Tunnels In Rockmentioning
confidence: 99%